Creating Decentralised SMART Manufacturing Units with a Newly Implemented Standard Communication Protocol - Gericke, Gareth A. (Central University of Technology, 2021)
Communication protocols drive the flow of information from machine to machine. However, with the requirements of the Fourth Industrial Revolution and machines set to become more mobile, flexible and intelligent, greater communication practices are required to fully incorporate this revolution. Machines are required less to be able to communicate in fixed networks with numerical representation, but rather to have the ability to communicate with machines swopping in and out of manufacturing lines and networks, all while adhering to real-time communication regulations. Furthermore, with machines swapping in and out, a greater need is placed on this communication protocol to operate in a purely decentralised manner, something not available on the market today. All these requirements aid each other. While machines are able to become decentralised and self-efficient, they rely on more crucial information, which is used to create intelligent decisions and execute them with timely precision. This dissertation entails an extensive research in communication protocols and their use in the manufacturing scene. From this, a newly developed communication protocol is designed with a heavy focus placed on real-time execution in a decentralised manner. The communication protocol is tested in a constructed water bottling plant to gauge its effectiveness and performance. Finally, conclusions are drawn from these results, detailing and elaborating the use of the communication protocol and the practices it ensues.
Dissertation